G GAMBARAN RESPONSE TIME PASIEN DI IGD RSI SITI AISYAH MADIUN - Filia Icha Sukamto (LPPM Universitas Sari Mulia, 2021)
Background: Response time is the speed in handling patients, calculated from the time the patient arrives until treatment is done, a good response time for patients is â‰¤ 5 minutes. The sooner the patient gets definitive help, the greater the likelihood of a person's recovery and survival, on the other hand, failure to respond to the emergency response time in the ER can be fatal in the form of death or permanent disability. Purpose: This study was to describe the response time of patients in the emergency room at RSI Siti Aisyah Madiun. Methods: This type of research is descriptive, with the patient population in the emergency department of RSI Siti Aisyah Madiun. The sample of the study was some of the patients in the ER, the sampling technique was quota sampling with a sample size of 92 respondents. Data collection techniques with observation sheets for response time and patient emergency categories. Univariate data analysis by percentage. Results: The results of the study of 92 respondents showed that 72 (78.3%) respondents were handled with a fast response time (<5 minutes) and 20 (21.7%) respondents were handled with a slow response time (> 5 minutes). Conclusion: Based on the results of this study, it is suggested that emergency room officers should always be more alert / responsive in handling emergency patients so that one of the indicators of service quality in the emergency room can be achieved, namely response time < 5 minutes.